Rosja w polskim filmie dokumentalnym na przykładzie projektu Rosja–Polska. Nowe spojrzenie - Brzezińska, Marta (Acta Polono-Ruthenica, 2015)
The aim of the article is to present images of Russia made by young Polish documentary filmmakers during the workshop project Russia–Poland. New gaze, which appears as the voice in the discussion about the mutual perception of Poles and Russians. Representations of Russia presented by Polish directors seems to me interesting in the context of film history and literary tradition, fragments of observed reality and its cinematic interpretation. As the result, we receive the record of relationship with the neighbor which involves a lot of contexts and is negotiated in tension between stereotype and the attempt of breaking it.